2014
DOI: 10.1007/s12206-014-1109-z
|View full text |Cite
|
Sign up to set email alerts
|

Strain behaviors of solder bump with underfill for flip chip package under thermal loading condition

Abstract: Since the introduction of Cu/low-k as the interconnect material, the chip-package interaction (CPI) has become a critical reliability challenge for flip chip packages. Revision of underfill material must be considered, which compromises the life of flip chip interconnect by releasing the stresses transferred to the silicon devices from the solder bumps, and thereby maintain the overall package reliability. Thus, it is important to understand the thermo-mechanical behavior of solder bumps. In this study, the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The use of DIC for the inspection of joined assemblies under thermal loading has mainly focused on soldered joints in electronics packaging and assembly. In the study of Kwak et al [31] DIC was used to capture the thermo-mechanical behaviour of soldered joints, obtaining the deformations and strain development in a temperature range between 25 °C to 100°C. Tominaga et al [32] observed the thermally induced strain development between 30 °C to 230°C in bi-metal assemblies via DIC, aiming to establish a measurement system of thermal deformations in electronic packages.…”
Section: Figure 1: Failure In a Pmma-glass Bonded Assembly Subjected ...mentioning
confidence: 99%
“…The use of DIC for the inspection of joined assemblies under thermal loading has mainly focused on soldered joints in electronics packaging and assembly. In the study of Kwak et al [31] DIC was used to capture the thermo-mechanical behaviour of soldered joints, obtaining the deformations and strain development in a temperature range between 25 °C to 100°C. Tominaga et al [32] observed the thermally induced strain development between 30 °C to 230°C in bi-metal assemblies via DIC, aiming to establish a measurement system of thermal deformations in electronic packages.…”
Section: Figure 1: Failure In a Pmma-glass Bonded Assembly Subjected ...mentioning
confidence: 99%
“…These days, DIC technology is also used in the electronics industry due to its robustness and high accuracy. There have been studies conducted using two-dimensional DIC technique to analyze solder joint reliability (Kwak, 2014; Yaofeng and Pang, 2008; Zhang et al , 2005). In particular, publications introducing technical implementations of 3D DIC for electronic components are increasing (Falk et al , 2019; Lim et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among various measuring methods, the application of microscope combined with Digital Image Correlation (DIC) has proven to be an effective experimental method. [12][13][14] By use of high-powered microscope to record the motion of speckle pattern on the material surface before and after deformation, the displacement information can be extracted by the correlation algorithm. Therefore, for the interaction between neural electrode and tissue, it can be inferred that displacement and strain field of the tissue could be obtained using this measuring method.…”
Section: Introductionmentioning
confidence: 99%